Retrospective and New Theoretical Proposals on Peace Education - Elena Anatolievna Zhizhko; Gali-Aleksandra Beltrán; Martín Beltrán-Saucedo (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
The goal of this documentary-bibliographic research, the results of which we present in this article, was to outline the general panorama of the evolution of the epistemological and institutional foundations of the culture of peace and its promotion through education. The authors found that, since the 1940s, the construction of a culture of peace has been a priority on the agenda of international and national governing bodies concerned with human development. Education emerges as the key factor in building harmonious human relationships based on the principles of peace, tolerance, and respect for the Other. Yet the educational models that have operated until now are insufficient to meet the demands of 21st-century individuals, who must navigate increasingly complex realities. Achieving a culture of peace through education is possible only by establishing a new type of pedagogy, complexity education, that enables students to understand the perplexities and fluctuations of the present moment. This model should foster intellectual curiosity and analytical intelligence; the capacity to generate non-standardized solutions and alternative approaches to problems; the ability to listen to and assimilate the discourse of others, re-examine one’s own perspectives, overcome prejudice, and cultivate empathy.